THE USE OF STUDENT CENTERED-LEARNING (SCL) TO DEVELOP STUDENTS’ SPEAKING SKILL - Uswatun Hasanah; Anshari Syafar (e-Journal of ELTS (English Language Teaching Society), 2021)
The objective of this research is to find out the effect of the Student-Centered Learning (SCL) technique to develop the speaking skill of second grade students. This research applied the experimental design of quasi-experiments. The population of this research was the second-grade students that were XI IPA 4 as experimental class and XI IPA 2 as control class. In sample selection, the research sample was selected using the convenience sampling technique to determine the sample. The data were collected through pre-test and post-test. Data were analyzed using t-test to compare the mean score of the pre-test and the post-test from experimental and control groups .The results showed that the mean differences in the classical abilities of the control and experimental class students were 45.1 and 49 in the pre-test, while the post-test were 61.16 and 55.29. Further analysis indicates t-counted (3.85) is greater than the t-tables (1.67)which means that the use of SCL has an impact on students’ speaking achievement. Therefore, the hypothesis of this research is accepted which means there is an improvement in their ability in speaking.